Estimation of substitution and transformation elasticities for South African trade - Liisa Saikkonen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The objective of this paper is to estimate transformation and Armington substitution elasticities for South African trade. We use linear methods to estimate elasticities without growth factors. We then employ a non-linear system of equations to estimate Armington import elasticities and related growth factors. Using the linear estimation method, we find positive (0.386-1.379) short-run Armington substitution elasticities for most studied industries. Moreover, positive transformation elasticities for exports contradict our assumption that increased relative export prices result in increased exports. The results of the non-linear estimation suggest that growth affects imports more than domestic consumption of domestic production in the manufacturing industry.
Keywords: F1; 330; South Africa; trade; Armington elasticity; constant elasticity of transformation